Analysis of Bangladesh tyre market perspective of CEAT Bangladesh Ltd - Shifat, Arfanul Hoque (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.